(الفصائل الدموية وعلاقتها بمؤشر كتلة الجسم وضغط الدم) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Obesity is a public health problem that affects all age groups in the population. High blood pressure is a chronic medical condition associated with vague symptoms. ABO blood groups are one of the basic types of genetic factors that can give important information for early detection of populations at risk. This study aimed to evaluate the effect of different blood groups on body mass index and blood pressure. This study included 100 participants (38 males and 62 females) aged (20-82 years) who were selected from March 2 Hospital, Sebha, in the period from October 2020 To February 2021. To calculate blood pressure and body mass index (BMI), the most prevalent groups in the study population were A+, O + by 27% of the total number of samples, followed by B + by 15%, B- by 10%, AB + by 6%, and AB- by 3% and finally A- by 2%. The most prevalent blood group was in the first age group (20-40 years old) group A + and the second age group (41-61 years) the most prevalent blood group was O +, and the third age group (62-82 years) was most A +. This study concluded that there were no statistically significant differences between the prevalence of overweight, blood pressure, and blood groups. However, the most prevalent groups in hypertensive patients are A+(34.7% ), followed by O+ 26.5%) and it was the most prevalent group in overweight patients. The excess is also A + (32.7%, followed by O + 25.5%), and the most prevalent blood group in males is O + 28.9% followed by A +15.8%) and in females A + (33.9%), followed by O + 25.8%) Despite this, the high incidence of stress and obesity requires more awareness and educational programs.